THE EFFECT OF SELF-DISCLOSURE ON EMOTIONAL REGULATION WITH THE MEDIATION OF FAMILY SUPPORT IN HIGH SCHOOL STUDENTS - Rani Nainggolan; Hasanuddin; Suryani Hardjo (International Journal of Cultural and Social Science, 2026)
Adolescence is a developmental stage characterized by significant biological, cognitive, and socio-emotional changes that require effective emotion regulation. This study aimed to examine the effect of self-disclosure on emotion regulation among high school students, with family support as a mediating variable. A quantitative approach was used with a population of 632 students and a sample of 200 respondents selected through random sampling. Data were collected using Likert-scale questionnaires, including the Revised Self-Disclosure Scale, the Emotion Regulation Questionnaire (Gross & John, 2003), and the Family Support Scale. Data analysis was conducted using SEM-PLS with JASP 0.19.3.0. The results showed that several self-disclosure dimensions significantly influenced emotion regulation. Intended disclosure (Beta = 0.190; p = 0.007), honesty-accuracy (Beta = 0.144; p = 0.040), and control of general depth (Beta = 0.170; p = 0.020) had a positive effect on cognitive reappraisal. The amount factor (Beta = 0.281; p < 0.001), honesty-accuracy (Beta = 0.150; p = 0.030), and control of general depth (Beta = 0.206; p = 0.004) significantly affected expressive suppression. Overall, self-disclosure contributed more consistently to emotion regulation and perceived family support than the direct effect of family support on emotion regulation. These findings highlight the importance of self-disclosure and supportive family environments in improving students’ emotion regulation abilities.